Development of an Automated Access Control and Management System for Enhanced Security in Industrial Facilities - Horban, A. (My University, 2024)
This paper presents the development and design of an automated access control and management system (AACMS) for industrial facilities. The structural diagram integrates key modules such as facial recognition and RFID-based identification, ensuring multi-factor authentication for enhanced security. The system includes a camera for biometric facial recognition, an RFID reader for card-based identification, and an electronic lock mechanism. A microprocessor module (MM) acts as the control unit, processing data from the RFID module and communicating with a laptop or single-board computer. The system operates by scanning both the user’s face and RFID card, verifying the data, and providing access if both criteria are met. The integration of these two identification methods – biometric (facial recognition) and RFID – ensures a robust and secure access control process, improving the overall safety of the industrial facility
Keywords: automated access control; RFID Identification; Multi-Factor Authentication; Industrial Security